APLIKASI ABU SEKAM PADI DAN KOMPOS TKKS PADA PADI GOGO (Oryza sativa L.) DI AREAL GAWANGAN KELAPA SAWIT PADA LAHAN GAMBUT - Bernatal Manurung; Jurnawaty Sjofjan; Armaini ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This research was aimed to determine the effect of rice husk ash and empty oil palm bunches (EOPB) compost on the growth and production of field rice at hall of oil palm area on peatland. The research was conducted at the experimental farm of the Agricultural Faculty University of Riau, Rimbo Panjang, Kampar from June to October 2014. The design used in this research are arranged in a Factorial Completely Randomized Block Design (RBD) consiting of two factor with three replication. The first factor are: Aplication of rice husk ash (S) with 4 dosage level (tons/ha), namely: S0 (0), S1 (2,5), S2 (5), S3 (7,5) and the second faktor are: Aplication of empty full bunch compost (T) with 3 dosage level (tons/ha), namely: T0 (0), T1 (2,5), T2 (5). The data obtained by analysis of variance (ANOVA) was tested further by Duncan’s New Multiple Range Test (DNMRT) at the level of 5%. The result showed the aplication of rice husk ash 5 tons/ha and empty oil palm bunches compost 5 tons/ha gives the highest yield in vegetative and generative phase, but equal by aplication of rice husk ash 0 tons/ha and empty oil palm bunches compost 5 tons/ha in generative phase. Empty oil palm bunches compost 5 tons/ha without rice husk ash did not differ significantly with the aplication of rice husk ash 5 – 7,5 tons/ha and empty oil palm bunches compost 5 tons/ha at dry weight /plot. Keywords: Rice Husk Ash, EOPB Compost, Field Rice, Hall of Oil Palm Area, Peatland